문서의 감정 분류를 위한 주목 방법 기반의 딥러닝 인코더 - 권순재(Sunjae Kwon); 김주애(Juae Kim); 강상우(Sangwoo Kang); 서정연(Jungyun Seo) (정보과학회 컴퓨팅의 실제 논문지, 2017)
Recently, deep learning encoder-based approach has been actively applied in the field of sentiment classification. However, Long Short-Term Memory network deep learning encoder, the commonly used architecture, lacks the quality of vector representation when the length of the documents is prolonged. In this study, for effective classification of the sentiment documents, we suggest the use of attention method-based deep learning encoder that generates document vector representation by weighted sum of the outputs of Long Short-Term Memory network based on importance. In addition, we propose methods to modify the attention method-based deep learning encoder to suit the sentiment classification field, which consist of a part that is to applied to window attention method and an attention weight adjustment part. In the window attention method part, the weights are obtained in the window units to effectively recognize feeling features that consist of more than one word. In the attention weight adjustment part, the learned weights are smoothened. Experimental results revealed that the performance of the proposed method outperformed Long Short-Term Memory network encoder, showing 89.67% in accuracy criteria. 최근 감정 분류 분야에서 딥러닝 인코더 기반의 접근 방법이 활발히 적용되고 있다. 딥러닝 인코더 기반의 접근 방법은 가변 길이 문장을 고정 길이 문서 벡터로 압축하여 표현한다. 하지만 딥러닝 인코더에 흔히 사용되는 구조인 장 단기 기억망(Long Short-Term Memory network) 딥러닝 인코더는 문서가 길어지는 경우, 문서 벡터 표현의 품질이 저하된다고 알려져 있다. 본 논문에서는 효과적인 감정 문서의 분류를 위해, 장 단기 기억망의 출력을 중요도에 따라 가중합하여 문서 벡터 표현을 생성하는 주목방법 기반의 딥러닝 인코더를 사용하는 것을 제안한다. 또한, 주목 방법 기반의 딥러닝 인코더를 문서의 감정 분류 영역에 맞게 수정하는 방법을 제안한다. 제안하는 방법은 윈도우 주목 방법(Window Attention Method)을 적용한 단계와 주목 가중치 재조정(Weight Adjustment) 단계로 구성된다. 윈도우 주목 방법은 한 단어 이상으로 구성된 감정 자질을 효과적으로 인식하기 위해, 윈도우 단위로 가중치를 학습한다. 주목 가중치 재조정에서는 학습된 가중치를 평활화(Smoothing) 한다, 실험 결과, 본 논문에서 제안하는 방법은 정확도 기준으로 89.67%의 성능을 나타내어 장 단기 기억망 인코더보다 높은 성능을 보였다.